Recovering bodies : illness, disability, and life-writing - Couser, G. Thomas (Madison : University of Wisconsin Press, 1997)
"A compelling look at personal narratives of HIV/AIDS, breast cancer paralysis, and deafness, Recovering Bodies examines many forms of life writing - including memoirs, diaries, collaborative narratives, photo documentaries, and essays - to illuminate the ways in which these narratives address the stigma of illness and disability. G. Thomas Couser shows that such books are not primarily records of medical conditions; they are instead a means for individuals to reclaim their bodies (or those of loved ones) from marginalization and impersonal medical discourse, by telling their stories in their own terms." "Couser considers why and under what circumstances individuals choose to write about illness or disability; what role plot plays in such narratives; how closure is achieved; who assumes the prerogative of narration; which conditions are most often represented; and which literary conventions lend themselves to representing particular conditions. By tracing the development of new subgenres of personal narrative in our time, this book explores how explicit consideration of illness and disability has enriched the repertoire of life writing. In addition, Couser's discussion of medical discourse joins the current debate about whether the biomedical model is entirely conducive to humane care for ill and disabled people." "With its sympathetic critique of the testimony of those most affected by these conditions, Recovering Bodies contributes to an understanding of the relations among bodily dysfunction, cultural conventions, and identity in contemporary America."--Jacket.
Machine generated contents note: 1. Introduction: Human Conditions -- Illness, Disability, and Life Writing -- 2. Medical Discourse and Subjectivity -- 3. Self-Reconstruction: Personal Narratives of Breast Cancer -- 4. HIV/AIDS and Its Stories -- 5. Crossing (Out) the Border: Autobiography and Physical Disability -- 6. Signs of Life: Deafness and Personal Narrative -- 7. Epilogue: The Value of Body Stories.
Includes bibliographical references (pages 299-310) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Sick -- United States -- Biography -- History and criticism; People with disabilities -- United States -- Biography -- History and criticism; Sick -- United States -- Psychology; People with disabilities -- United States -- Psychology; Autobiography; Biography as a literary form; AIDS (Disease); People with disabilities; Biography; Acquired Immunodeficiency Syndrome; Breast Neoplasms; Disabled Persons; Persons with Hearing Disabilities; Autobiographies as Topic; Biographies as Topic; Personnes handicapées -- États-Unis -- Biographies -- Histoire et critique; Malades -- États-Unis -- Psychologie; Personnes handicapées -- États-Unis -- Psychologie; Autobiographie; Biographie (Genre littéraire); Sida; Personnes handicapées.; Biographies; autobiography (genre); biographies (literary works); biography (general genre); MEDICAL -- Evidence-Based Medicine; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; MEDICAL -- Internal Medicine; MEDICAL -- Clinical Medicine; People with disabilities; Autobiography; Biography as a literary form; People with disabilities -- Psychology; Sick -- Biography; Sick -- Psychology; United States; AIDS (Disease); Clinical Psychology; Psychiatry; Health & Biological Sciences; Autobiography; Personal Narrative; Personal narratives; Autobiographies; Criticism, interpretation, etc; Personal narratives; Récits personnels